One-year follow-up of a randomized trial with a dilemma-focused intervention for depression: exploring an alternative to problem-oriented strategies (2018)
Background Cognitive behavioural therapy (CBT) is aimed to counteract cognitions and behaviours that are considered as dysfunctional. The aim of the study is to test whether the inclusion of a non-counteractive approach (dilemma-focused intervention, DFI) in combination with CBT group therapy will yield better short- and long-term outcomes than an intervention conducted entirely using CBT. Method A total of 128 patients with depression and at least one cognitive conflict, of six health community centres in Barcelona, participated from November of 2011 to December of 2014 in seven weekly group CBT sessions and were then randomly allocated to either DFI or CBT (eight individual sessions each) by an independent researcher. Depressive symptoms were assessed with the Beck Depression Inventory-II at baseline, at the end of therapy and three- and twelve-month follow-ups. Therapists did not participate in any of the assessments nor in the randomisation of patients and evaluators were masked to group assignment. Both intention to treat and complete case analyses were performed using linear mixed models with random effects. Findings According to intention-to-treat analysis (F2, 179 = 0.69) and complete case analysis (F2, 146 = 0.88), both conditions similarly reduced the severity of symptoms across posttreatment assessments. For the 77 participants (CBTgroup +CBTindividual = 40; CBTgroup+DFIindividual = 37) that completed allocated treatment and one-year follow-up assessment, response and remission rates were relative higher for the DFI condition, however no significant differences were found between treatment conditions. The relapse rates were similar between treatment conditions (CBTgroup +CBTindividual = 7/20; CBTgroup+DFIindividual = 8/22). Interpretation Although using a counteractive approach across all the treatment sessions is quite effective, it does not seem to be necessary to produce significant improvement. DFI may be considered as an alternative, which could be included in a wider treatment for depression.